Capital account convertibility, poor developing countries, and international financial architecture - Gilbert, Christopher L. (2001)
Deals with international financial architecture and the poor developing countries. Discusses the extent to which poor developing countries sholuld move towards capital account convertibility. Focuses on the extent to which, within the current international financial architecture, international institutions are able to come to the assistance of countries which have liberalised and do encounter crises. Argues that there is a key weakness in the architecture.